From Exclusivism to Pluralism: Shifting Perspective of the Gereja Protestan Maluku (GPM) in Interreligious Relations - Rachel Iwamony (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2019)
This article aims to find out and describe the shifting position of the GPM (Gereja Protestan Maluku) as to other religions, especially Islam. Through library research towards some important documents of the GPM, the researcher found out the development of theological perspectives of the GPM which are fundamental and important for the GPM in understanding other religions. In studying these documents, this study discovered that the position of the GPM as to other religions before the social conflict in 1999 and 2004 are differ significantly to that of after the social conflict. In the document of PIP/RIPP in the period of 1995 to 2005, before the social conflict, they described clearly that the GPM recognizes other religions as the object of its mission. In contrast, in the same document of the period of 2005 to 2015, after the social conflict, they state that the GPM embraces other religions as its partner. Even in the newest document of Ajaran Gereja GPM, they state that God in Jesus Christ is the Savior of all human beings without religious categories. These theological notions have a significant impact on the GPM in shaping its relation with other religions. Not only the theological normative notion, but also the cultural perspectives such as Pela have opened the possibility for the Moluccan Moslems and Christians to coexist as brothers and sisters.